Experience of organizing BCG therapy for localized bladder cancer in outpatient cancer care centers - Sergey A. Parts; Yana V. Gridneva; Maria I. Volkova; Albert V. Oskarev; Ogulshat R. Sinitsyna; Evgeniya S. Kuzmina; Vsevolod N. Galkin; Saida M. Gadzhieva (ZAO "Consilium Medicum", 2024)
Background. The clinical course of non-muscle-invasive bladder cancer is characterized by a tendency to develop local recurrences and the ability to tumor progression. The most effective method of preventing disease progression after transurethral resection of the bladder in patients of intermediate and high-risk groups is intravesical therapy with BCG antitumor vaccine containing attenuated Mycobacterium tuberculosis. Taking into account the increasing incidence non-muscle-invasive bladder cancer in Moscow, the organization of adequate use of BCG vaccine in clinical practice requires the involvement of significant organizational and human resources. Aim. To develop and validate an organizational model for the delivery of BCG therapy for non-muscle-invasive bladder cancer at an outpatient cancer care center using hospital-substitution technologies. Materials and methods. In the period from June 2023 to May 2024, BCG therapy has been performed in Oncology Center №1 of Yudin Moscow City Hospital in 180 patients with verified non-muscle-invasive bladder cancer of intermediate and high-risk groups. Results. The study revealed a trend towards an increase in the absolute number of early bladder cancer in Moscow in the period 2018-2023. According to clinical guidelines, treatment of patients with non-muscle-invasive bladder cancer includes determination of the risk of recurrence and tumor progression with subsequent formation of indications for intravesical BCG therapy. The regimen of administration depending on the risk of recurrence includes 18-42 instillations for 12-36 months after transurethral resection of the bladder with follow-up examinations every three months. The procedure of intravesical BCG therapy takes 1-2 hours and does not require hospitalization. An organizational model of treatment an outpatient cancer care center based on various forms of hospital-substitution technologies is presented. Conclusion. Intravesical BCG therapy is a highly demanded method for the treatment of non-muscle-invasive bladder cancer. This method can be widely used in outpatient settings through the use of hospital-substitution technologies.